3D-modeling of the spine using EOS imaging system: inter-reader reproducibility and reliability - Rehm, Johannes; Germann, Thomas; Akbar, Michael; Pepke, Wojciech; Kauczor, Hans-Ulrich; Weber, Marc-André; Spira, Daniel (PLOS ONE, 2017)
Objectives To retrospectively assess the interreader reproducibility and reliability of EOS 3D full spine reconstructions in patients with adolescent idiopathic scoliosis (AIS). Methods 73 patients with mean age of 17 years and a moderate AIS (median Cobb Angle 18.2°) obtained low-dose standing biplanar radiographs with EOS. Two independent readers performed “full spine” 3D reconstructions of the spine with the “full-spine” method adjusting the bone contour of every thoracic and lumbar vertebra (Th1-L5). Interreader reproducibility was assessed regarding rotation of every single vertebra in the coronal (i.e. frontal), sagittal (i.e. lateral), and axial plane, T1/T12 kyphosis, T4/T12 kyphosis, L1/L5 lordosis, L1/S1 lordosis and pelvic parameters. Radiation exposure, scan-time and 3D reconstruction time were recorded. Results Interclass correlation (ICC) ranged between 0.83 and 0.98 for frontal vertebral rotation, between 0.94 and 0.99 for lateral vertebral rotation and between 0.51 and 0.88 for axial vertebral rotation. ICC was 0.92 for T1/T12 kyphosis, 0.95 for T4/T12 kyphosis, 0.90 for L1/L5 lordosis, 0.85 for L1/S1 lordosis, 0.97 for pelvic incidence, 0.96 for sacral slope, 0.98 for sagittal pelvic tilt and 0.94 for lateral pelvic tilt. The mean time for reconstruction was 14.9 minutes (reader 1: 14.6 minutes, reader 2: 15.2 minutes, p<0.0001). The mean total absorbed dose was 593.4μGy ±212.3 per patient. Conclusion EOS “full spine” 3D angle measurement of vertebral rotation proved to be reliable and was performed in an acceptable reconstruction time. Interreader reproducibility of axial rotation was limited to some degree in the upper and middle thoracic spine due the obtuse angulation of the pedicles and the processi spinosi in the frontal view somewhat complicating their delineation.
Gesehen am 26.04.2018